Promotion of the equal access of girls and women to technical and vocational education - (:unkn) unknown (Unesco, 1996)
"This UNEVOC publication is addressed to policy-makers, administrators, planners, teachers, specialists and all those interested in the issue of promotion of the equal acces of girls and women to technical and vocational education. Compiled by the Section for Technical and Vocational Education, UNESCO, Paris, this monograph includes the final report of the UNEVOC International Expert Meeting on the Promotion of Equal Access of Girls and Women to Technical and Vocational Education held in Seoul, Republic of Korea, in July 1995 and the country discussion papers submitted by the participants fo this event." (Editor,BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; P 1.3 Frauen; G 2.4.5 Gender Mainstreaming; S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; Berufsbildungspolitik; Gewerblich-technische Berufsbildung; Frauen; Mädchen; Geschlechtsspezifische Faktoren; Chancengleichheit; Gleichberechtigung; Bildungsbericht